2004
DOI: 10.1177/004051750407400602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boric Acid and BTCA on Tensile Strength Loss of Finished Cotton Fabrics

Abstract: Several polycarboxylic acids have been studied as durable press finishing agents for cotton fabrics. The most effective is 1,2,3,4-butanetetracarboxylic acid (BTCA). One of the drawbacks of this crosslinking is the severe loss of mechanical strength of the treated fabrics, which is responsible for the reduced durability of finished cotton garments. In this research, boric acid mixed with BTCA is considered as a remedy for this problem. Fourier transform infrared spectra, tensile tests, and crease recovery angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 5 publications
2
37
0
1
Order By: Relevance
“…[1][2][3][4][5] The crosslinking reaction is enhanced by catalysts, such as sodium hypophosulfite (SHP) and titanium dioxide (TiO 2 ). [6][7][8][9][10][11] To enhance the BTCA treatment with TiO 2 , the surface modification of the cotton fiber is required.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The crosslinking reaction is enhanced by catalysts, such as sodium hypophosulfite (SHP) and titanium dioxide (TiO 2 ). [6][7][8][9][10][11] To enhance the BTCA treatment with TiO 2 , the surface modification of the cotton fiber is required.…”
Section: Introductionmentioning
confidence: 99%
“…In general, BTCA-treated cellulosic fabrics suffer a major loss of such mechanical properties as tensile strength, tear strength, and abrasion resistance because of two key contributing factors; the acidity of the polycarboxylic acid at high temperature and the restriction of stress distribution within the fibers because of the crosslinking between cellulosic polymers. 14,16 However, there was no significant difference in the tensile strengths between the BTCA-treated cotton fabrics and the 0.1M 4-hydroxybenzophenone/BTCA-treated cotton fabrics. Also it was observed that the average tensile strength of the 0.1M 4-hydroxybenzophenone/BTCA-treated cotton fabrics hardly changed after 10 h UV illumination [ Fig.…”
Section: Surface and Mechanical Properties Of Benzophenone Chromophormentioning
confidence: 87%
“…13,14 The reaction of polycarboxylic acid with cellulosic polymers occurs through esterification of hydroxyl groups, although not all the carboxylic acids will be able to react with the cellulosic substrate. The effective polycarboxylic acids contain three or more carboxylic groups and those groups are capable of forming five-or six-member cyclic anhydride rings.…”
Section: Preparation Of Benzophenone Chromophoric Group Incorporated mentioning
confidence: 99%
“…This is due to the fact that crosslinkers react with the hydroxyl groups in cellulose molecules with primary chemical bonds (Lam et al 2010;Trask-Morrell et al 1994;Sricharussin et al 2004;Dehadabi 2012;Peng 2012). Previous studies have shown that the crosslinking agents can interact with nanoparticles of titanium dioxide to improve the adhesion between cellulose molecules, but these carboxylic acids need to have at least two free carboxylic groups to be able to bind to both cotton and TiO 2 (Montazer et al 2012;Karimi et al 2010).…”
Section: Introductionmentioning
confidence: 99%